PEMBUATAN DAN UJI MUTU FISIK SEDIAAN SALEP KULIT DARI EKSTRAK BIJI KAKAO (Theobroma cacao L.) - Rusmin, Rusmin (Akademi Farmasi Yamasi Makassar, 2025)
Abstract. This research aims to make a preparation of cocoa bean extract (Theobroma cacao L.) skin ointment that meets the requirements for a good physical quality test for skin ointment using vaseline album and adeps lanae ointment bases. Cocoa beans (Theobroma cacao L.) were extracted using the maceration method using 96% ethanol then the extraction results were made into 3 skin ointment preparations with the same base and using cocoa bean extract (Theobroma cacao L.) with a concentration of 5% b/b, 10 % b/b, and 15% b/b. The research results show that skin ointment preparations with extract concentrations of 5% b/b, 10% b/b, and 15% b/b can meet the physical quality test parameters including organoletic tests which produce a semi-solid form, distinctive odor, brown color, test homogeneity obtained homogeneous results, the pH test obtained a pH of 5 which met the skin pH requirements of 4.5 – 6.5, the spreadability test obtained results for a concentration of 5% b/b resulting in a spreadability of 5.2 cm, a concentration of 10% b/b b produced 5.6 cm, and a concentration of 15% b/b produced 6.5 cm, where this result met the standard requirements for good ointment spreadability in the range of 5 - 7 cm, and the adhesive test produced 20 - 37 seconds. Where this result meets the adhesion requirement, namely more than 4 seconds.